Prostacyclin-producing human mesenchymal cells target H19 lncRNA to augment endogenous progenitor function in hindlimb ischaemia - Deng, Yuxiao (Nat Commun, 2016)
Promoting the paracrine effects of human mesenchymal stem cell (hMSC) therapy may contribute to improvements in patient outcomes. Here we develop an innovative strategy to enhance the paracrine effects of hMSCs. In a mouse hindlimb ischaemia model, we examine the effects of hMSCs in which a novel triple-catalytic enzyme is introduced to stably produce prostacyclin (PGI(2)-hMSCs). We show that PGI(2)-hMSCs facilitate perfusion recovery and enhance running capability as compared with control hMSCs or iloprost (a stable PGI(2) analogue). Transplanted PGI(2)-hMSCs do not incorporate long term into host tissue, but rather they mediate host regeneration and muscle mass gain in a paracrine manner. Mechanistically, this involves long noncoding RNA H19 in promoting PGI(2)-hMSC-associated survival and proliferation of host progenitor cells under hypoxic conditions. Together, our data reveal the novel ability of PGI(2)-hMSCs to stimulate host regenerative processes and improve physical function by regulating long noncoding RNA in resident progenitor cells.